Promoting the healing of infected diabetic wound by an anti-bacterial and nano-enzyme-containing hydrogel with inflammation-suppressing, ROS-scavenging, oxygen and nitric oxide-generating properties - Tu, Chenxi; Lu, Huidan; Zhou, Tong; Zhang, Wanying; Deng, Liwen; Cao, Wangbei; Yang, Zhijian; Wang, Zhaolong; Wu, Xinyu; Ding, Jie; Xu, Feng; Gao, Changyou (Biomaterials, 2022)
The diabetic wound is easily to develop into a chronic wound because of the extremely serious and complex inflammatory microenvironment including biofilm formation, over-expressed reactive oxygen species (ROS), hypoxia and insufficiency of nitric oxide (NO) synthesis. In this work, a multifunctional hydrogel was designed and prepared by crosslinking hydrophilic poly(PEGMA-co-GMA-co-AAm) (PPGA) polymers with hyperbranched poly-L-lysine (HBPL)-modified manganese dioxide (MnO2) nanozymes. Pravastatin sodium, which is supposed to participate in the synthesis of NO, was further loaded to obtain the HMP hydrogel. The capabilities of this hydrogel in scavenging different types of ROS, generating O2, killing broad spectrum bacteria, and protecting cells against oxidative stress were confirmed in vitro. The transcriptome analysis revealed that HBPL inhibited bacterial quorum sensing (QS) system, downregulated virulent genes, and interfered bacterial metabolism. The HBPL-crosslinked hydrogels killed up to 94.1%–99.5% of methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli (E. coli) and Pseudomonas aeruginosa even at 109 CFU/mL. HBPL modification greatly increased the stability of MnO2 nanosheets in physiological environment. The MRSA-caused infection was effectively treated by the HBPL-crosslinked HMP hydrogel in vivo, and thereby the wound closure at inflammatory phase was promoted significantly. The treatment of HMP hydrogel reduced the ROS degree and relieved the inflammatory level significantly, accompanied by the decreased neutrophil infiltration and enhanced M2-type macrophage polarization in vivo. Significantly lower levels of inflammatory factors such as interleukin-1β (IL-1β), IL-6, tumor necrosis factor-α (TNF-α) and chemokines-1 (CXCL-1), and higher levels of anti-inflammatory cytokines such as IL-4 and IL-10 were also confirmed. Moreover, the HMP hydrogel could promote the secretion of transforming growth factor-β (TGF-β) and stimulate neovascularization, and deposition of collagen with a thicker skin and epithelium structure.